Special Issue “Advances in Performance Analysis and Technology in Sports” - Łukasz Rydzik; Tadeusz Ambroży; Tomasz Pałka (Applied Sciences)
In recent years, the landscape of sports science has been profoundly transformed by rapid advances in performance analysis and the integration of innovative technologies [...]